The Role of Family and Teachers in Reproductive Health Literacy of Adolescent Girls in Coastal Areas in Iwoimendaa District, Kolaka Regency - Yusniatin, Yusniatin; Umi Nurlila, Ratna; Nofitasari, Ari (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction: According to data from the Iwoimendaa Community Health Center, nine teenagers became pregnant outside of marriage between July and December 2023. Furthermore, some women neglect their reproductive systems, leading to reproductive health problems, including unpleasant odors and sexually transmitted infections. Therefore, the researchers investigated the role of families and teachers in improving reproductive health literacy among adolescent girls in the coastal areas of Iwoimendaa District, Kolaka Regency. Method:This quantitative analytical research used a cross-sectional study design, with independent and dependent variables measured simultaneously. The population was all 180 female adolescents at MAN 2 Kolaka, and the sample consisted of 125 adolescents. The sample was determined using the Slovin formula. Result:The correlation test shows a phi value of 0.076, which means there is a very weak relationship between the role of the family and a phi value of 0.535, which means there is a moderate relationship between the role of teachers and health literacy of adolescent girls in the coastal area of ​​Iwoimendaa sub-district, Kolaka district. Conclusion:There is a relationship between the role of the family and the role of teachers with health literacy of adolescent girls in the coastal area of ​​Iwoimendaa sub-district, Kolaka district.